Halal Supply Chain Management (HSCM) in Traditional Poultry Markets: A Case Study of Wonokromo and Asem, Surabaya - Supriyanto, Aan (Halal Science, 2025)
The rapid expansion of the halal economy has created challenges in ensuring compliance within traditional markets, where regulatory frameworks often diverge from everyday consumer practices. This study examines the implementation of Halal Supply Chain Management (HSCM) in two traditional poultry markets in Surabaya Wonokromo and Asem by assessing halal certification, operational practices, and consumer purchasing behavior. A qualitative case study design was applied using purposive sampling to recruit 20 participants, including farmers, distributors, slaughterhouse operators, retailers, and consumers. Data were collected through semi-structured interviews, systematic observations, and document analysis conducted between August and November 2019. The document analysis involved halal certificates, market permits, and regulatory guidelines, supporting triangulation of findings. Although the data were collected in 2019, they remain relevant because structural conditions in traditional markets and consumer purchasing patterns have not changed substantially in recent years. Findings show that Wonokromo Market uses slaughterhouses certified by the Majelis Ulama Indonesia (MUI), yet certification has minimal influence on buyer decisions. Most consumers prioritize freshness (72%), price (65%), and proximity (58%), while only 22% consider halal labels important. Asem Market, meanwhile, follows halal-compliant slaughtering practices despite lacking formal certification, largely due to low consumer demand and limited regulatory accessibility. The study concludes that halal certification enhances procedural credibility but has limited economic and behavioral impact in traditional markets, where trust is shaped primarily by cultural norms, vendor familiarity, and direct product assessment. Strengthening halal assurance systems therefore requires integrated strategies that combine consumer education, policy incentives, and more accessible certification mechanisms.